2012
DOI: 10.3402/ejpt.v3i0.7382
|View full text |Cite
|
Sign up to set email alerts
|

Post- and peritraumatic stress in disaster survivors: an explorative study about the influence of individual and event characteristics across different types of disasters

Abstract: BackgroundExamination of existing research on posttraumatic adjustment after disasters suggests that survivors’ posttraumatic stress levels might be better understood by investigating the influence of the characteristics of the event experienced on how people thought and felt, during the event as well as afterwards.ObjectiveTo compare survivors’ perceived post- and peritraumatic emotional and cognitive reactions across different types of disasters. Additionally, to investigate individual and event characterist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
37
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 40 publications
1
37
0
2
Order By: Relevance
“…Here, it must be noted that all scenarios described a situation of similar risk, from the stage of realization, to the stage where an evacuation was being initiated, through to the stage of a participant reaching a place of complete safety. Regarding differences in peritraumatic fear and cognition related to the type of scenario, it should be noted that other recent research studies have found significant differences in survivors" post-and peritraumatic stress depending on the type of disaster they had experienced (Grimm, Hulse, Preiss, & Schmidt, 2011b;Shakespeare-Finch & Armstrong, 2010). One possible explanation regarding the scenario effect on personal risk might be that participants were primed; that is, if a participant was given a scenario describing a terror attack for instance, the scenario itself may have increased salience of terror attacks in the participant"s mind, which might have then resulted in higher levels of concern of becoming a victim of a terror attack.…”
Section: Discussionmentioning
confidence: 95%
“…Here, it must be noted that all scenarios described a situation of similar risk, from the stage of realization, to the stage where an evacuation was being initiated, through to the stage of a participant reaching a place of complete safety. Regarding differences in peritraumatic fear and cognition related to the type of scenario, it should be noted that other recent research studies have found significant differences in survivors" post-and peritraumatic stress depending on the type of disaster they had experienced (Grimm, Hulse, Preiss, & Schmidt, 2011b;Shakespeare-Finch & Armstrong, 2010). One possible explanation regarding the scenario effect on personal risk might be that participants were primed; that is, if a participant was given a scenario describing a terror attack for instance, the scenario itself may have increased salience of terror attacks in the participant"s mind, which might have then resulted in higher levels of concern of becoming a victim of a terror attack.…”
Section: Discussionmentioning
confidence: 95%
“…There is support for diverse subtypes of such manifestations, although it is unclear what factors influence symptom presentations and if they are relevant to the course of the disorder (Breslau, Reboussin, Anthony, & Storr, 2005). One possibility is that variations in exposure and secondary stressors may lead to differences in symptom presentation, and that these presentations differ in the persistence of the symptoms (Grimm, Hulse, Preiss, & Schmidt, 2012; Rosellini, Coffey, Tracy, & Galea, 2014). …”
Section: Introductionmentioning
confidence: 99%
“…The three most common themes in both studies were control and reasoning, general threat of injury and death, and uncertain threat. Grimm et al examined peritraumatic cognitive content and processes associated with narratives after both natural and manmade disasters (e.g., earthquake, terror attack, bus accident, building collapse; Freitag et al, 2011;Grimm et al, 2012aGrimm et al, , 2012b. Grimm et al examined peritraumatic cognitive content and processes associated with narratives after both natural and manmade disasters (e.g., earthquake, terror attack, bus accident, building collapse; Freitag et al, 2011;Grimm et al, 2012aGrimm et al, , 2012b.…”
mentioning
confidence: 99%